Tumour necrosis factor α secretion induces protease activation and acinar cell necrosis in acute experimental pancreatitis in mice. Issue 3 (5th April 2012) - Sendler, Matthias; Dummer, Annegret; Weiss, Frank U; Krüger, Burkhard; Wartmann, Thomas; Scharffetter-Kochanek, Karin; van Rooijen, Nico; Malla, Sudarshan Ravi; Aghdassi, Ali; Halangk, Walter; Lerch, Markus M; Mayerle, Julia
Abstract : Background: Acute pancreatitis has long been considered a disorder of pancreatic self-digestion, in which intracellular activation of digestive proteases induces tissue injury. Chemokines, released from damaged pancreatic cells then attract inflammatory cells, whose systemic action ultimately determines the disease severity. In the present work the opposite mechanism is investigated; that is, whether and how inflammatory cells can activate intracellular proteases. Design: Using mice either deficient for the CD18-α subunit of the membrane attack complex-1 (MAC-1) complex or tumour necrosis factor (TNF)α, as well as after depletion of leucocyte subpopulations, pancreatitis was induced by 7-hourly caerulein injections (50 μg/kg, intraperitoneally). Pancreatic acini were coincubated in vitro from wild-type and cathepsin-B-deficient animals with phorbol-12-myristate-13-acetate (PMA)-activated neutrophils and macrophages, caerulein or TNFα, and activities of trypsin, cathepsin-B and caspase-3 were measured, as well as necrosis using fluorogenic substrates. TNFα was inhibited with monospecific antibodies. Results: Deletion of CD18 prevented transmigration of leucocytes into the pancreas during pancreatitis, greatly reduced disease severity and abolished digestive protease activation. Depletion of neutrophils and macrophages equally reduced premature trypsinogen activation and disease severity. In vitro activated neutrophils and macrophages directly induced premature protease activation and cell death in pancreatic acini and stimulation of acini with TNFα induced caspase-3 activation and necrosis via a cathepsin-B and calcium-dependent mechanism. Neutralising antibodies against TNFα and genetic deletion of TNFα prevented leucocyte-induced trypsin activity and necrosis in isolated acini. Conclusions: The soluble inflammatory cell mediator TNFα directly induces premature protease activation and necrosis in pancreatic acinar cells. This activation depends on calcium and cathepsin-B activity. The findings from the present work further suggest that targeting TNFα, for which pharmaceutical agents are readily available, could be an effective treatment strategy that directly addresses the cellular causes of pancreatitis.